High-strength room-temperature self-repairing lignin / polyurethane composite elastomer as well as preparation method and application thereof
By introducing lignin and metal ions into polyurethane, using metal coordination bonds and multiple interactions, the problems of poor dispersion and high self-repair temperature of lignin-based polyurethane elastomers are solved, and lignin is achieved with high strength and room temperature self-repair /Polyurethane composite elastomer meets practical application needs and reduces the use of petrochemical resources.
Patent Information
- Application Number
- CN202411254208.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-09
AI Technical Summary
The existing lignin-based polyurethane elastomers have problems such as poor dispersion, low mechanical properties and high self-repair temperature, which is difficult to meet the needs of high strength and room temperature self-repair.
Long-chain diol reacts with isocyanate, hydrazide and oxime chain extenders to construct the polyurethane hard segment, and introduces lignin and metal ions to improve compatibility and energy dissipation mechanisms through metal coordination bonds, combining multiple mutuals Acts to achieve high intensity and room temperature self-healing.
The prepared lignin/polyurethane composite elastomer has a tensile strength higher than 20MPa, a self-repair efficiency exceeds 80%, and achieves high-efficiency self-repair at room temperature to meet practical application needs, while reducing dependence on petrochemical resources.
Smart Images

Figure BDA0005033470050000111 
Figure HDA0005033470060000011 
Figure HDA0005033470060000012
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyurethane elastomers, and particularly relates to a high-strength, room-temperature self-repairing lignin / polyurethane composite elastomer and a preparation method and application thereof. Background Art
[0002] Polyurethane is a block polymer composed of alternating flexible segments and rigid segments, with a highly adjustable microphase separation structure. Due to its good wear resistance, high elasticity, processability and biocompatibility, it is widely used in the automotive, military, biomedicine and other fields.
[0003] However, due to the complex application environment of polyurethane elastomers, they will inevitably be subjected to external impact, static load, friction and other effects during use, which can easily cause damage such as microcracks in the elastomer, seriously affecting its reliability and service life. With the increasing demand for material durability, self-repairing polyurethanes have received widespread attention. Generally, the self-repairing effect depends on dynamic interactions, including dynamic covalent bonds (such as disulfide bonds, borate bonds, oxime urethane bonds, etc.) and dynamic non-covalent bonds (such as hydrogen bonds, metal coordination bonds, host-guest interactions, etc.). By introducing dynamic reversible bonds into the polyurethane network, when the material is damaged, these dynamic bonds can spontaneously dissociate and reorganize, thereby repairing mechanical or chemical damage.
[0004] In addition, most polyurethane elastomers are prepared based on non-renewable petroleum-based raw materials, and the use of a large amount of petrochemical resources has caused serious resource consumption and environmental problems. Therefore, the development of polyurethane elastomers also urgently needs to enter a new era of high efficiency, green, safety and multifunctionality. Lignin is the most abundant and only natural aromatic polymer in nature. Due to its high rigidity, renewability and high hydroxyl content, it is expected to replace some petroleum-based raw materials for the synthesis of bio-based polyurethane elastomers. In addition, lignin also has excellent antibacterial properties, UV resistance and photothermal conversion capabilities, which is conducive to the development of multifunctional applications of lignin composite elastomers. Although lignin has great application potential and has been widely studied in recent years, lignin has poor dispersibility in polymers and is easy to agglomerate, resulting in its compatibility with polyurethane matrices. In addition, since lignin is a rigid multifunctional structure, the prepared lignin-based polyurethane is usually cross-linked, which seriously reduces the dynamic properties of the elastomer and limits its multifunctional applications.
[0005] Patent CN113754851A discloses a method for preparing a self-repairable lignin-based polyurethane elastomer containing disulfide bonds. Although the prepared elastomer can achieve a self-repair efficiency of more than 90% at 60°C, its maximum tensile strength does not exceed 20MPa, and its mechanical properties are poor, making it difficult to meet practical application requirements.
[0006] Patent CN116903820A discloses a method for increasing the hydroxyl content of lignin by hydroxylation modification, and preparing self-repairable lignin-based polyurethane using modified lignin and DA chain extender. Although the modification improves the reactivity and compatibility of lignin with the matrix, the prepared elastomer has a tensile strength of 29MPa and a self-repair efficiency of 100%. However, its self-repair temperature is as high as 130°C, which is difficult to achieve in daily applications.
[0007] Patent CN115677972A discloses a method for preparing self-repairing lignin-based polyurethane by constructing dynamic phenolic hydroxylamine bonds and metal coordination bonds between lignin and the matrix. Although the double cross-linked network based on lignin makes the elastomer have a tensile strength of more than 30MPa, and a self-repair rate of more than 95% can be achieved under infrared light for 10 minutes, the actual repair temperature under infrared light irradiation exceeds 100°C.
[0008] Patent CN113817130A discloses a method for preparing lignin-based polyurethane by using a low-boiling point and low-toxicity solvent to extract lignin. Although the process is relatively environmentally friendly and the tensile strength of the prepared polyurethane exceeds 40MPa, its self-healing ability is not explored.
[0009] In summary, the lignin-based polyurethanes reported so far still have the following problems: First, because lignin is easy to self-aggregate and has poor dispersion in the matrix, the prepared lignin-based polyurethanes have low compatibility and poor mechanical properties. Second, the polyurethanes prepared using lignin are usually cross-linked structures, which makes it impossible to achieve self-repair or the self-repair temperature is too high (usually over 100°C), and even difficult to recycle and reuse. Summary of the invention
[0010] In order to overcome the shortcomings and deficiencies in the prior art, the primary purpose of the present invention is to provide a method for preparing a high-strength, room-temperature self-healing lignin / polyurethane composite elastomer.
[0011] Another object of the present invention is to provide a lignin / polyurethane composite elastomer prepared by the above preparation method.
[0012] Another object of the present invention is to provide an application of the above-mentioned lignin / polyurethane composite elastomer.
[0013] The purpose of the present invention is achieved through the following technical solutions:
[0014] A method for preparing a high-strength, room-temperature self-healing lignin / polyurethane composite elastomer comprises the following steps:
[0015] (1) The long-chain diol is vacuum dehydrated at 90-120° C. for 0.5-4 h, then cooled to 60-90° C., dissolved in an organic solvent, a catalyst and an isocyanate are added, and stirred for reaction for 1-4 h to obtain a polyurethane prepolymer, and then the reaction temperature is lowered to 25-60° C., a hydrazide chain extender and a dioxime chain extender are added, and the reaction is continued for 2-8 h to obtain a polyurethane solution.
[0016] (2) dissolving lignin and metal ions in an organic solvent, adding the solution to the polyurethane solution obtained in step (1), stirring at 300-1000 rpm at room temperature for 0.5-3 hours, pouring the solution into a mold and drying at 60-120° C. to remove the solvent, thereby obtaining a high-strength, room-temperature self-healing lignin / polyurethane composite elastomer.
[0017] The relative molecular weight of the long-chain diol in step (1) is 1000-4000, specifically one or more of polyethylene glycol, polybutylene glycol, polycaprolactone glycol, polytetramethylene glycol, and polycarbonate glycol;
[0018] The organic solvent is one or both of N,N-dimethylformamide and dimethyl sulfoxide;
[0019] The catalyst is dibutyltin dilaurate;
[0020] The isocyanate is one or more of toluene diisocyanate, isophorone diisocyanate, and tetramethylxylylene diisocyanate;
[0021] The hydrazide chain extender is one or more of carbohydrazide, oxalic acid dihydrazide, succinic acid dihydrazide, adipic acid dihydrazide, and isophthalic acid dihydrazide;
[0022] The dioxime chain extender is one or more of diacetyl oxime, p-benzoquinone dioxime, 2,4-pentanedione dioxime, and 1,2-cyclohexanedione dioxime.
[0023] The lignin in step (2) is one or more of alkali lignin, enzymatic lignin, and organic solvent lignin;
[0024] The metal ions are one or more of copper ions, iron ions and zinc ions, and are specifically metal ions provided by one or more of the following metal salts: copper chloride, copper oxide, iron chloride, zinc chloride, zinc oxide, zinc acetate and zinc methacrylate.
[0025] The molar ratio of the long-chain diol, isocyanate, hydrazide chain extender and dioxime chain extender in step (1) is 1:2-4:0.1-2:0.1-2; the amount of the catalyst is 0.1% of the total mass of the long-chain diol, isocyanate, hydrazide chain extender and dioxime chain extender.
[0026] The relative molecular mass of the lignin in step (2) is between 1800 and 2100, the polydispersity index is between 1 and 1.2, and the hydroxyl content is 4 to 5 mmol / g; the amount of the lignin used is 1 to 20% of the mass of the long-chain diol in step (1).
[0027] The molar ratio of the metal ion in step (2) to the dioxime chain extender in step (1) is 1:1-3.
[0028] A lignin / polyurethane composite elastomer prepared by the above preparation method, wherein the tensile strength of the lignin / polyurethane composite elastomer is higher than 20MPa, and can even reach above 40MPa, the self-healing temperature is room temperature (≈35°C), and the self-healing efficiency is higher than 80%, and can even exceed 90%.
[0029] The above-mentioned lignin / polyurethane composite elastomer is used in the fields of flexible drive and solar thermal power generation.
[0030] The principle of the present invention is:
[0031] The present invention uses irregular isocyanate to react with hydrazide and oxime chain extenders to form polyurethane hard segments. Hydrazide chain extenders provide abundant hydrogen bond interactions, oxime chain extenders can undergo dynamic reversible reactions and provide abundant N atom ligands for metal coordination bonds, and irregular isocyanate can avoid excessive aggregation of hard segments and ensure their dynamic performance. Lignin is introduced as a green and environmentally friendly toughening agent to improve the mechanical properties of polyurethane. The key is that the introduction of Zn 2+ The construction of abundant metal coordination bonds between lignin and oxime urethane not only effectively improves the compatibility between lignin and polyurethane, but also provides an excellent energy dissipation mechanism for the composite material. While further improving the mechanical properties of the elastomer, its excellent dynamic properties are also maintained. In addition, the constraints of multiple interactions enable the prepared elastomer to maintain the stability of the network structure at room temperature, and will not spontaneously fuse due to contact or overlap between different regions of the elastomer, but can achieve high-efficiency self-repair at room temperature after decoupling with a trace amount of ethanol solvent. This reasonable combination strategy of flexible matrix and rigid lignin enables the prepared lignin / polyurethane composite elastomer to have the characteristics of high strength and room temperature self-repair.
[0032] Compared with the prior art, the present invention has the following advantages and effects:
[0033] (1) The present invention uses dynamically reversible hydrazide and oxime chain extenders, which not only provide excellent dynamic properties for the elastomer, but also provide abundant ligands for metal coordination bonds.
[0034] (2) The present invention introduces Zn 2+, rich metal coordination bonds were constructed between lignin and oxime amine, effectively improving the compatibility of the two phases.
[0035] (3) The lignin / polyurethane composite elastomer prepared by the present invention has stable multiple interactions, which enables the elastomer to accurately switch between stable and excellent mechanical properties and high-efficiency self-repair at room temperature to meet practical application requirements.
[0036] (4) The lignin / polyurethane composite elastomer prepared by the present invention reduces the demand and dependence of polyurethane on petrochemical resources and realizes the high-value utilization of lignin. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a preparation route for lignin / polyurethane composite elastomer.
[0038] Figure 2 It is the infrared spectra of Examples 1-4 and Comparative Example 1.
[0039] Figure 3 The SEM images of Example 2 and Comparative Example 2 are shown.
[0040] Figure 4 These are the SEM images of Example 2 before and after self-repair. DETAILED DESCRIPTION
[0041] The present invention is further described below with reference to specific embodiments and drawings, but they should not be construed as limiting the present invention.
[0042] Tensile test conditions: The heat-dried elastomer was cut into standard dumbbell-shaped samples with a length of 50 mm, a narrow width of 4 mm, a narrow length of 17 mm, and a thickness of 1 mm. The stretching interval was 30 mm. The test was carried out using an electronic universal testing machine (* / Inspekt Table Blue 5KN, Hegewald & Peschke, Germany). The test temperature was room temperature and the stretching rate was 50 mm / min.
[0043] Self-healing test conditions: The sample was completely cut in the middle, then the cut was closed, 50 μL of ethanol solution was added, and it was placed at 35°C for 24 hours. The self-healing efficiency of the repaired sample was evaluated by tensile test.
[0044] Structural characterization: Fourier transform infrared spectrometer (Thermo-Fisher, USA) was used in attenuated total reflectance (ATR) mode with a scanning range of 400–4000 cm -1 , the number of scans is 32 times.
[0045] Microstructure analysis: The samples were characterized using a field emission scanning electron microscope (SEM) (SU8220, Hitachi, Japan).
[0046] The synthetic route of lignin-based polyurethane elastomer in the following examples is as follows Figure 1 shown.
[0047] Example 1
[0048] 1. Weigh 5 parts by mass of polytetramethylene glycol (Mn=2000) and vacuum dry it at 110°C for 2h to remove moisture; then cool to 80°C, add 10 parts by mass of N,N-dimethylformamide, 1.7 parts by mass of isophorone diisocyanate, and 0.01 parts by mass of a catalyst, and stir and react at 300rpm for 3h to obtain a polyurethane prepolymer solution; then lower the temperature to 50°C, add 0.4 parts by mass of adipic acid dihydrazide and 0.3 parts by mass of dimethylglyoxime, and continue to react for 3h to obtain a polyurethane solution.
[0049] 2. Dissolve 0.125 parts by mass of alkali lignin and 0.2 parts by mass of zinc chloride in 5 parts by mass of N,N-dimethylformamide, add to the polyurethane solution obtained in step 1, stir at 600 rpm at room temperature for 1 hour, then pour the solution into a polytetrafluoroethylene mold, dry at 80°C for 24 hours to remove the solvent, and obtain a high-strength, room-temperature self-healing lignin / polyurethane composite elastomer.
[0050] Example 2
[0051] 1. Same as Example 1.
[0052] 2. Dissolve 0.25 parts by mass of alkali lignin and 0.2 parts by mass of zinc chloride in 5 parts by mass of N,N-dimethylformamide, add to the polyurethane solution obtained in step 1, stir at 600 rpm at room temperature for 1 hour, then pour the solution into a polytetrafluoroethylene mold, dry at 80°C for 24 hours to remove the solvent, and obtain a high-strength, room-temperature self-healing lignin / polyurethane composite elastomer.
[0053] Example 3
[0054] 1. Same as Example 1.
[0055] 2. Dissolve 0.375 parts by mass of alkali lignin and 0.2 parts by mass of zinc chloride in 5 parts by mass of N,N-dimethylformamide, add to the polyurethane solution obtained in step 1, stir at 600 rpm at room temperature for 1 hour, then pour the solution into a polytetrafluoroethylene mold, dry at 80°C for 24 hours to remove the solvent, and obtain a high-strength, room-temperature self-healing lignin / polyurethane composite elastomer.
[0056] Example 4
[0057] 1. Same as Example 1.
[0058] 2. Dissolve 0.5 parts by mass of alkali lignin and 0.2 parts by mass of zinc chloride in 5 parts by mass of N,N-dimethylformamide, add to the polyurethane solution obtained in step 1, stir at 600 rpm at room temperature for 1 hour, then pour the solution into a polytetrafluoroethylene mold, dry at 80°C for 24 hours to remove the solvent, and obtain a high-strength, room-temperature self-healing lignin / polyurethane composite elastomer.
[0059] Example 5
[0060] 1. Same as Example 1.
[0061] 2. Dissolve 0.25 parts by mass of alkali lignin and 0.1 parts by mass of zinc chloride in 5 parts by mass of N,N-dimethylformamide, add to the polyurethane solution obtained in step 1, stir at 600 rpm at room temperature for 1 hour, then pour the solution into a polytetrafluoroethylene mold, dry at 80°C for 24 hours to remove the solvent, and obtain a high-strength, room-temperature self-healing lignin / polyurethane composite elastomer.
[0062] Example 6
[0063] 1. Same as Example 1.
[0064] 2. Dissolve 0.25 parts by mass of alkali lignin and 0.3 parts by mass of zinc chloride in 5 parts by mass of N,N-dimethylformamide, add to the polyurethane solution obtained in step 1, stir at 600 rpm at room temperature for 1 hour, then pour the solution into a polytetrafluoroethylene mold, dry at 80°C for 24 hours to remove the solvent, and obtain a high-strength, room-temperature self-healing lignin / polyurethane composite elastomer.
[0065] Example 7
[0066] 1. Weigh 5 parts by mass of polytetramethylene glycol (Mn=2000) and vacuum dry it at 110°C for 2h to remove moisture; then cool to 80°C, add 10 parts by mass of N,N-dimethylformamide, 1.7 parts by mass of isophorone diisocyanate, and 0.01 parts by mass of a catalyst, and stir and react at 300rpm for 3h to obtain a polyurethane prepolymer solution; then lower the temperature to 50°C, add 0.6 parts by mass of adipic acid dihydrazide and 0.15 parts by mass of dimethylglyoxime, and continue to react for 3h to obtain a polyurethane solution.
[0067] 2. Same as Example 2.
[0068] Example 8
[0069] 1. Weigh 5 parts by mass of polytetramethylene glycol (Mn=2000) and vacuum dry it at 110°C for 2h to remove moisture; then cool to 80°C, add 10 parts by mass of N,N-dimethylformamide, 1.7 parts by mass of isophorone diisocyanate, and 0.01 parts by mass of a catalyst, and stir and react at 300rpm for 3h to obtain a polyurethane prepolymer solution; then lower the temperature to 50°C, add 0.2 parts by mass of adipic acid dihydrazide and 0.45 parts by mass of dimethylglyoxime, and continue to react for 3h to obtain a polyurethane solution.
[0070] 2. Same as Example 2.
[0071] Comparative Example 1
[0072] 1. Weigh 5 parts by mass of polytetrahydrofuran ether diol (Mn = 2000) and vacuum dry at 110 ° C for 2 hours to remove moisture; then cool to 80 ° C, add 10 parts by mass of N, N-dimethylformamide, 1.7 parts by mass of isophorone diisocyanate, 0.01 parts by mass of catalyst, stir and react at 300 rpm for 3 hours to obtain a polyurethane prepolymer solution; then reduce the temperature to 50 ° C, add 0.4 parts by mass of adipic acid dihydrazide, 0.3 parts by mass of dimethylglyoxime, and continue to react for 3 hours to obtain a polyurethane solution. Then pour the solution into a polytetrafluoroethylene mold, dry at 80 ° C for 24 hours to remove the solvent, and obtain a composite elastomer.
[0073] Comparative Example 2
[0074] 1. Same as Example 1.
[0075] 2. Dissolve 0.25 parts by mass of alkali lignin in 5 parts by mass of N,N-dimethylformamide, add to the polyurethane solution obtained in step 1, stir at 600 rpm at room temperature for 1 hour, then pour the solution into a polytetrafluoroethylene mold, dry at 80°C for 24 hours to remove the solvent, and obtain a composite elastomer.
[0076] Comparative Example 3
[0077] 1. Same as Example 1.
[0078] 2. Dissolve 0.2 parts by mass of zinc chloride in 5 parts by mass of N,N-dimethylformamide, add to the polyurethane solution obtained in step 1, stir at 600 rpm at room temperature for 1 hour, then pour the solution into a polytetrafluoroethylene mold, dry at 80°C for 24 hours to remove the solvent, and obtain a composite elastomer.
[0079] Comparative Example 4
[0080] 1. Weigh 5 parts by mass of polytetramethylene glycol (Mn=2000) and vacuum dry it at 110°C for 2h to remove moisture; then cool it to 80°C, add 10 parts by mass of N,N-dimethylformamide, 1.7 parts by mass of isophorone diisocyanate, and 0.01 parts by mass of a catalyst, and stir the mixture at 300rpm for 3h to obtain a polyurethane prepolymer solution; then lower the temperature to 50°C, add 0.8 parts by mass of adipic acid dihydrazide, and continue the reaction for 3h to obtain a polyurethane solution.
[0081] 2. Same as Example 2, finally obtaining a composite elastomer.
[0082] Comparative Example 5
[0083] 1. Weigh 5 parts by mass of polytetramethylene glycol (Mn=2000) and vacuum dry it at 110°C for 2h to remove moisture; then cool to 80°C, add 10 parts by mass of N,N-dimethylformamide, 1.7 parts by mass of isophorone diisocyanate, and 0.01 parts by mass of a catalyst, and stir and react at 300rpm for 3h to obtain a polyurethane prepolymer solution; then lower the temperature to 50°C, add 0.6 parts by mass of dimethylglyoxime, and continue to react for 3h to obtain a polyurethane solution.
[0084] 2. Same as Example 2, finally obtaining a composite elastomer.
[0085] The elastomers obtained in Examples 1-8 and Comparative Examples 1-5 were tested for various mechanical properties such as tensile strength, elongation at break, and self-repair rate. The results are shown in Table 1.
[0086] Table 1 Mechanical properties of Examples 1-8 and Comparative Examples 1-5
[0087]
[0088] As can be seen from Table 1, the mechanical properties of the composite elastomer prepared with lignin are greatly improved compared with the elastomer without lignin, and the excellent self-healing efficiency is maintained. 2+ Compared with the lignin / polyurethane composite elastomer without Zn introduction, 2+ The mechanical properties of the elastomer are also effectively improved, indicating that the construction of metal coordination bonds improves the compatibility of lignin and the polyurethane matrix, allowing lignin to fully exert its toughening effect, while also providing an excellent energy dissipation mechanism for the composite system.
[0089] Figure 2 The infrared spectra of the elastomers prepared in Comparative Example 1 and Examples 1-4 are shown in Table 1. All samples were prepared at 3300 cm -1 and 1650cm -1There are obvious absorption peaks at 985cm, which correspond to the stretching vibration absorption peaks of NH and C=O. These two peaks are typical characteristic peaks of polyurethane structure. -1 The vibration absorption peak representing the NO bond appears at 2270 cm -1 No absorption peak representing isocyanate was observed, indicating that isocyanate had been completely consumed and the polyurethane elastomer was successfully synthesized.
[0090] Figure 3 The SEM images of Example 2 and Comparative Example 2 show that the lignin particles in Example 2 are evenly distributed in the polyurethane matrix, and the particle sizes are relatively close. However, the lignin particles in Comparative Example 2 are severely agglomerated, and the particle sizes vary greatly. This indicates that Zn 2+ The introduction of enhances the compatibility and dispersibility of lignin with the polyurethane matrix.
[0091] Figure 4 The SEM images before and after self-repair of Example 2. It can be seen that after 24 hours of repair, the cut on the sample disappeared and the surface morphology returned to flatness, indicating that the sample has basically completed self-repair.
[0092] The above embodiments are relatively suitable implementation modes of the present invention. The implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations and simplifications made without departing from the spirit and principle of the present invention shall be equivalent replacement modes and shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a high-strength, room-temperature self-repairing lignin / polyurethane composite elastomer, characterized in that The steps include: (1) vacuum dehydrating a long-chain diol at 90-120° C. for 0.5-4 h, then cooling to 60-90° C., dissolving in an organic solvent, adding a catalyst and an isocyanate, stirring and reacting for 1-4 h to obtain a polyurethane prepolymer, then lowering the reaction temperature to 25-60° C., adding a hydrazide chain extender and a dioxime chain extender, and continuing the reaction for 2-8 h to obtain a polyurethane solution; (2) dissolving lignin and metal ions in an organic solvent, adding the solution to the polyurethane solution obtained in step (1), stirring at 300-1000 rpm at room temperature for 0.5-3 hours, pouring the solution into a mold and drying at 60-120° C. to remove the solvent, thereby obtaining a high-strength, room-temperature self-healing lignin / polyurethane composite elastomer.
2. The method for preparing a high-strength, room temperature self-healing lignin / polyurethane composite elastomer according to claim 1, characterized in that: The relative molecular weight of the long-chain diol in step (1) is 1000-4000, specifically one or more of polyethylene glycol, polybutylene glycol, polycaprolactone glycol, polytetramethylene glycol, and polycarbonate glycol; The organic solvent is one or two of N,N-dimethylformamide and dimethyl sulfoxide; The catalyst is dibutyltin dilaurate; The isocyanate is one or more of toluene diisocyanate, isophorone diisocyanate, and tetramethylxylylene diisocyanate; The hydrazide chain extender is one or more of carbohydrazide, oxalic acid dihydrazide, succinic acid dihydrazide, adipic acid dihydrazide, and isophthalic acid dihydrazide; The dioxime chain extender is one or more of diacetyl oxime, p-benzoquinone dioxime, 2,4-pentanedione dioxime, and 1,2-cyclohexanedione dioxime.
3. The method for preparing a high-strength, room temperature self-healing lignin / polyurethane composite elastomer according to claim 1, characterized in that: The lignin in step (2) is one or more of alkali lignin, enzymatic lignin, and organic solvent lignin; The metal ions are one or more of copper ions, iron ions and zinc ions, and are specifically metal ions provided by one or more of the following metal salts: copper chloride, copper oxide, iron chloride, zinc chloride, zinc oxide, zinc acetate and zinc methacrylate.
4. The method for preparing a high-strength, room temperature self-healing lignin / polyurethane composite elastomer according to claim 1, characterized in that: The molar ratio of the long-chain diol, isocyanate, hydrazide chain extender and dioxime chain extender in step (1) is 1:2-4:0.1-2:0.1-2; the amount of the catalyst is 0.1% of the total mass of the long-chain diol, isocyanate, hydrazide chain extender and dioxime chain extender.
5. The method for preparing a high-strength, room temperature self-healing lignin / polyurethane composite elastomer according to claim 1, characterized in that: The relative molecular mass of the lignin in step (2) is between 1800 and 2100, the polydispersity index is between 1 and 1.2, and the hydroxyl content is 4 to 5 mmol / g; the amount of the lignin used is 1 to 20% of the mass of the long-chain diol in step (1).
6. The method for preparing a high-strength, room temperature self-healing lignin / polyurethane composite elastomer according to claim 1, characterized in that: The molar ratio of the metal ion in step (2) to the dioxime chain extender in step (1) is 1:1-3.
7. A lignin / polyurethane composite elastomer prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The tensile strength of the lignin / polyurethane composite elastomer is higher than 20 MPa, the self-repairing temperature is room temperature, and the self-repairing efficiency is higher than 80%.
8. The lignin / polyurethane composite elastomer according to claim 7, characterized in that: The tensile strength of the lignin / polyurethane composite elastomer reaches above 40 MPa, and the self-repairing efficiency reaches above 90%.
9. Application of the lignin / polyurethane composite elastomer according to claim 7 in the fields of flexible drive and solar thermal power generation.
Citation Information
Patent Citations
Solvent-free lignin-based polyurethane elastomer capable of being repeatedly processed and preparation method of solvent-free lignin-based polyurethane elastomer
CN113817130A
Self-repairable lignin-containing polyurethane elastomer and preparation method thereof
CN113754851A
Lignin-based thermoplastic polyurethane elastomer material and preparation method thereof
CN114573784A
High-performance transparent room-temperature self-repairing polyurethane elastomer based on multiple reversible effects and preparation method of high-performance transparent room-temperature self-repairing polyurethane elastomer
CN114940740A
High-toughness self-repairing supramolecular polyurethane elastomer based on thiolactone chemistry and preparation method of high-toughness self-repairing supramolecular polyurethane elastomer
CN116217889A
Cited By
Polyurethane as well as preparation method and application thereof
CN121270859A
Polyurethane and method for its preparation and use
CN121270859B
